pengaruh PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF QUIZWHIZZER UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII D SMP NEGERI 1 GIRI: PENGARUH MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MINAT BELAJAR - Lita Ismania; agus Mursidi; Miskawi (Universitas Veteran Bangun Nusantara, 2026)
This research was motivated by the low learning interest of students in Social Studies (IPS) subjects in class VIII D at SMP Negeri 1 Giri. The dense material requiring memorization and the monotonous use of conventional methods caused students to become passive and easily bored. This study aimed to examine whether there is an influence, and how significant that influence is, of using the QuizWhizzer interactive learning media based on gamification to improve students' social studies learning interest. A quantitative approach with a Pre-experimental Design (One-Group Pretest-Posttest Design) was applied. A saturated sample consisting of 46 students from class VIII D at SMP Negeri 1 Giri was involved. Data were collected using a learning interest questionnaire/scale. Quantitative data analysis utilized parametric statistical different tests (Paired Samples T-Test) assisted by SPSS version 27 software, after the prerequisite normality test was met. The results of the descriptive analysis showed a substantial increase in the mean score of student learning interest from 24.83 (pre-test) to 35.63 (post-test), yielding an absolute increase of 10.80 points. The Paired Samples T-Test hypothesis testing resulted in a Sig. (2-tailed) value of 0.000 (< 0.05). This was supported by qualitative data from interview transcripts indicating high enthusiasm, where students felt happy, focused, and did not feel sleepy because the media presented an interactive and competitive quiz. In conclusion, the use of QuizWhizzer interactive learning media has a very significant and positive influence on improving the social studies learning interest of class VIII D students at SMP Negeri 1 Giri. The digital gamification platform proved capable of transforming the learning perception into an enjoyable experience, stimulating curiosity, and effectively enhancing students' cognitive and affective engagement in the social studies learning process. Keywords: Interactive Learning Media, QuizWhizzer, Learning Interest, Social Studies Education, Gamification